Agriculture in Algeria: a sectoral performance excluding hydrocarbons - Radhia ZEMIRLI; Souria HAMMACHE (Journal of Excellence for Economics and Management Research, 2017)
Since its independence, Algeria has sought to support agriculture because of its potential in this sector. Indeed, it has put in place several agricultural policies and the objective was to achieve food security by substituting local production for imported products.        From this point of view, the country implemented a policy from the 2000s through the National Agricultural Development Plan in an attempt to overcome dependence on imports of certain commodities, such as cereals, Dairy products and vegetable oils ... etc.    Moreover, the persistence and aggravation of the external shock, caused by the collapse of hydrocarbon prices, militates for the continuation and widening of agricultural or industrial investment or tourism, in order to promote both The diversification of the economy, the satisfaction of a greater proportion of the needs of the internal market by national production and the development of non-hydrocarbon exports, which are essential for the rebalancing of external trade.         Thus, our reflection finds its essence in the fact that agriculture has great potential to become a factor of development in Algeria and to constitute a strategy of economic diversification. In order to carry out our work, we relied on an empirical and theoretical literature, allowing us to structure our article as follows: the first will present the main characteristics of agriculture in Algeria, then the second point, analyze the performances realized In terms of agriculture, in particular through the various support strategies put in place, and a comparative analysis will be made between the agricultural sector and other sectors of activity in order to identify the importance of this sector for economic growth from the country.